RECOMMENDATIONS FOR WORK SYSTEM ASSESSMENT OF SNI 9001: 2008 IMPLEMENTATION BASED ON MACRO ERGONOMICS AT PT SPU - Heri Setiawan; Muhammad Yusuf; Micheline Rinamuti; Dominikus Budiarto; Yohanes Dicka Pratama; Achmad Alfian (Logic : Jurnal Rancang Bangun dan Teknologi, 2025)
The increasingly intense competition, the number of customer choice options and the more selective customers in choosing medical equipment products require PT SPU as one of the Indonesian National Medical Device (Alkes) industry engaged in the production process of medical devices and rehabilitation to always improve a better work system. To improve product quality PT SPU has implemented the SNI ISO 9001: 2008 Quality Management System which contains standard requirements used to measure the organisation's ability to meet customer requirements and appropriate regulations. The purpose of this research is to identify and assess how much influence each component of the work system has on the satisfaction of customers, employees and leaders. The method used is Macro Ergonomics. The magnitude of the contribution of the work assessment process of SNI ISO 9001: 2008 implementation to the influence of significant macro ergonomic aspects on organisational conditions (52.45%), physical environment (37.37%), production processes (12.53%), infrastructure (9.69%), production process services (5.90%), and R&D activities (2.82%).(3) Proposed recommendations for improving organisational conditions by confirming the roles and responsibilities of each person so that there are no undisciplined employees between sections, improving communication. Physical work environment by rearranging the place and rejuvenating production process support tools that are not ergonomic and have been damaged, redesigning a conducive and comfortable work environment. Production process improvements including employees actively communicating with each other and development of standard operating procedures (SOPs) with legacy competencies through knowledge transfer. Improvements to Facilities and Infrastructure by adding air conditioning, such as blower/exhaust ventilators, and sufficient room ventilation. Improvements to R&D: by facilitating employee exchanges for R&D activities, training, technical guidance, and experience exchange; increasing access to cooperation with government and private organisations.